EFEKTIVITAS PENGGUNAAN METODE PERMAINAN DENGAN MEDIA FLASHCARD DALAM MENINGKATKAN PEMBELAJARAN KOSAKATA ALAT TULIS BAHASA MANDARIN PADA SISWA SD X SURABAYA - Kristianto, Fennyta Anggelina; Apriana, Maria (Universitas Widya Kartika Surabaya, 2024)
Mandarin is needed today, many schools require learning Mandarin. The author found a problem in learningactivities at SD X Surabaya, namely learning media that is not supportive so that students do not have interestin learning. Therefore, to overcome problems in learning, the author uses flashcard game media, this learningfocuses on improving students' ability to write vocabulary. The research uses a quantitative method by takingthe results of the pre-test and post-test student scores which are then compared. From the results of thecalculation, it can be seen from the percentage of student completion, initially only 6.7%, now it is 100%,which has increased considerably, namely 93.3%. This shows that the increase in students' understanding ofthe vocabulary taught.